2018
DOI: 10.1080/00380253.2018.1526055
|View full text |Cite
|
Sign up to set email alerts
|

Drawing on LGB Identity to Encourage Participation and Disclosure of Sexual Orientation in Surveys

Abstract: This paper reports an experiment that tested how three survey cover designs-images of traditional families and individuals displaying themselves in typical gender ways; images of lesbian, gay, and bisexual (LGB) and heterosexual individuals and families; and no cover images-affected LGB people's participation and disclosure of LGB identity and non-LGB people's participation. Analyses showed the LGB-inclusive cover led to significantly more LGB respondents than the other designs, without significantly affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The increasing dimension of LGBT+ population looks undeniable, whether leaped by a real growth of this group or derived from a more confident report of their sexual identity, due to more tolerant attitudes toward LGBT+ communities (Johnson et al, 2001;Sharp, 2002), as showed by a clear evolution of Americans' views during the past 40 years (figure 1). On the other hand, despite the obstacles in accurately measure LGBT+ dimension, as confidential issues regarding surveys (Gates, 2017;Poux, 1998), methodology chosen and wording or questioning of the sexual orientation (Stange et al, 2019), and regardless the different statistics available, a continuous growth is generally accepted. This segment is generally assumed to account for 5-10% of the total population and it is estimated to increasing in most of the countries, with a 2.9 percent growth worldwide, between 2016 and 2018 (tables 1 and 2).…”
Section: The Dream Marketmentioning
confidence: 99%
“…The increasing dimension of LGBT+ population looks undeniable, whether leaped by a real growth of this group or derived from a more confident report of their sexual identity, due to more tolerant attitudes toward LGBT+ communities (Johnson et al, 2001;Sharp, 2002), as showed by a clear evolution of Americans' views during the past 40 years (figure 1). On the other hand, despite the obstacles in accurately measure LGBT+ dimension, as confidential issues regarding surveys (Gates, 2017;Poux, 1998), methodology chosen and wording or questioning of the sexual orientation (Stange et al, 2019), and regardless the different statistics available, a continuous growth is generally accepted. This segment is generally assumed to account for 5-10% of the total population and it is estimated to increasing in most of the countries, with a 2.9 percent growth worldwide, between 2016 and 2018 (tables 1 and 2).…”
Section: The Dream Marketmentioning
confidence: 99%